Calcific Plaque Modification by Acoustic Shock Waves: Intravascular Lithotripsy in Coronary Interventions. (January 2021) - Karimi Galougahi, Keyvan; Patel, Sanjay; Shlofmitz, Richard A.; Maehara, Akiko; Kereiakes, Dean J.; Hill, Jonathan M.; Stone, Gregg W.; Ali, Ziad A.
Abstract : Constituting a significant proportion of lesions treated with transcatheter interventions in the coronary arteries, moderate-to-severe calcification portends lower procedural success rates, increased periprocedural major adverse events, and unfavorable long-term clinical outcomes compared with noncalcific plaques. Adapted from the lithotripsy technology for treatment of nephrolithiasis, intravascular lithotripsy is a new technique for treatment of severely calcific lesions that uses acoustic shock waves in a balloon-based system to induce fracture in the calcium deposits to facilitate luminal gain and stent expansion. Herein, we summarize the physics and characteristics of the currently available intravascular lithotripsy system (Shockwave Medical, Santa Clara, CA), the clinical data on intravascular lithotripsy use in the coronary arteries, and future directions for adoption of the technique in percutaneous coronary intervention.